Pemanfaatan Mesin Pencacah Sampah Organik sebagai Upaya Pengolahan Sampah Berbasis Masyarakat - Shinta Naafia Permatasari; Prananda Aditia Ramadan; Marlinda Ina; Tiara Eka Agusrina; Kautzar Angger Sudarsono; Thesna Widya Fandhyta (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the utilization of an organic waste shredding machine as an effort to support community-based waste management. The research employed a descriptive qualitative approach using observation, interviews, and documentation to examine the implementation and impact of the machine on local waste processing practices. The results indicate that the use of the shredding machine effectively reduces the volume of organic waste and facilitates faster processing into compost materials. Community involvement in operating and maintaining the machine reflects increased awareness and responsibility toward environmentally friendly waste management. However, several challenges were identified, including limited technical knowledge and inconsistent machine usage. Despite these constraints, the utilization of the organic waste shredding machine has contributed positively to environmental cleanliness and encouraged community participation in sustainable waste management. Therefore, this program demonstrates significant potential to strengthen community-based waste processing systems when supported by continuous guidance and proper management.